Determinant of Earnings Management Practices of Manufacturing Companies in Indonesia - Kenny Ardillah (Perkumpulan Cendekia Muda Kreatif Indonesia, 2026)
The company's demands to achieve predetermined profit targets can be a motivation to carry out earnings management. This study aims to determine the effect of managerial ownership, accounting conservatism, and information asymmetry on earnings management. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The number of samples that match the criteria in the study was 29 companies using the purposive sampling method, and the amount of research data was 87 companies. The sampling was carried out using a regression data panel with common effects approach using Eviews 10. This study indicates that managerial ownership and accounting conservatism do not affect earnings management and that information asymmetry affects negatively to earnings management.